1986
DOI: 10.3109/00365528609034627
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in Crohn's Disease

Abstract: The incidence of cancer in Crohn's disease has been evaluated in 473 patients admitted to Rigshospitalet during the period 1 April 1964 to 1 January 1983. The patients' condition at the end of the survey, their survival, and the number and location of cancers were registered. During the survey period 23 cancers (4.9%) were found. Five were intestinal (1.1%) and were split evenly among the two sexes, whereas among 18 patients with extraintestinal cancers there was only 1 man. There was no increased risk of deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Those who were less than 30 years old at the time of diagnosis of CD had a higher relative risk than those diagnosed at an older age. In pa tients with any colonic involvement, diagno sis at an early age entailed a comparative risk of 20.9, compared with 2.2 in those diagnosed after age 30 [8], Four earlier population-based studies found no association between CD and colo rectal cancer [20][21][22][23], However, all four failed to correct their data for the small subsets of their populations that were actually at risk, namely those with extensive, long-standing, unresected colonic disease.…”
Section: Risk In CDmentioning
confidence: 78%
“…Those who were less than 30 years old at the time of diagnosis of CD had a higher relative risk than those diagnosed at an older age. In pa tients with any colonic involvement, diagno sis at an early age entailed a comparative risk of 20.9, compared with 2.2 in those diagnosed after age 30 [8], Four earlier population-based studies found no association between CD and colo rectal cancer [20][21][22][23], However, all four failed to correct their data for the small subsets of their populations that were actually at risk, namely those with extensive, long-standing, unresected colonic disease.…”
Section: Risk In CDmentioning
confidence: 78%
“…Otherwise, this may be due to differences in medical and surgical treatment. Higher colectomy rates in Denmark and Sweden may partially account for the difference observed in CRC risk [21]. Although based on a small number of cases, the overall risk of CRC is increased in Japanese patients with CD (SIR 5.80; 95% CI 2.13–12.68); this risk increase is mainly caused by rectal and anal canal/fistula cancer, not colon cancer, all CRC patients developed cancer, in these locations.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors support evidence of increased incidence of both large and small intestinal cancer among patients with longstanding CD [7,10]. However, the increased risk for small intestinal cancer is controversial and has not been confirmed by other studies [6,11]. It is hardly surprising that the association between CD and adenocarcinoma of the small bowel has been suggested on the basis of cumulated case reports and has not been statistically proven [6].…”
Section: Discussionmentioning
confidence: 95%